Ischemic colitis associated with colon cancer: ABOUT A CASE - Lanza, Mario; Rivero, Luis; Rudnitzky, Omar; Bermúdez, Jorge (Cirugía del Uruguay, 1982)
Report of one case of sigmoideal cancer associated with ischemic colitis stenosing stage. This is a rare association, probably due to the different evolutive forms of ischemic colopathy, or else to the fact they are not included in resected specimens. Preoperatory diagnosis is most useful -as with this patient- since it allows the surgeon to planified treatment prior to operation. Therapy is described highlighting the fact that in this instance- both lesions were treated in the same operation and were perfectly confirmed by anatomo-pathology.